2023
DOI: 10.3389/fendo.2023.1088944
|View full text |Cite
|
Sign up to set email alerts
|

Elafin is related to immune infiltration and could predict the poor prognosis in ovarian cancer

Abstract: BackgroundOvarian cancer (OC) is the most lethal gynecologic malignancy, yet the clinical results for OC patients are still variable. Therefore, we examined how elafin expression affects the patients’ prognoses and immunotherapy responses in OC, which may facilitate treatment selection and improve prognosis.MethodsThe elafin mRNA expression profile was downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus. Elafin’s prognostic potential and its relationship with clinical variables were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…High levels of PI3 are associated with severe disease severity in various cancers ( Hunt et al, 2013 ; Longatto-Filho et al, 2021 ), while another TCGA-OV analysis showed its prognostic value in OC ( Li J et al, 2020 ). Additionally, high elafin expression has been associated with unfavorable OS but better immunotherapy responses ( Lu et al, 2023 ). Recent studies have found that TGFBI CpG islands are hypermethylated in adjacent normal colon tissue, with the corresponding sequences showing hypomethylation in colon cancer tissue, and that higher TGFBI levels are associated with poorer prognosis ( Zhang H. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of PI3 are associated with severe disease severity in various cancers ( Hunt et al, 2013 ; Longatto-Filho et al, 2021 ), while another TCGA-OV analysis showed its prognostic value in OC ( Li J et al, 2020 ). Additionally, high elafin expression has been associated with unfavorable OS but better immunotherapy responses ( Lu et al, 2023 ). Recent studies have found that TGFBI CpG islands are hypermethylated in adjacent normal colon tissue, with the corresponding sequences showing hypomethylation in colon cancer tissue, and that higher TGFBI levels are associated with poorer prognosis ( Zhang H. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%